Developing Environmental Care Attitudes and Scientific Literacy through Sasi Local Wisdom-Based E-Modules - Rediani, Ni Nyoman; Kaize, Bernadetha Rizki; Hanifah , Sri; Nainggolan, Herrio Tekdi; Dharma Sanjaya, Pande Made; Hallatu, Trinovianto G.R (Jurnal Pedagogi dan Pembelajaran, 2023)
The lack of scientific literacy skills and environmental care attitudes possessed by students, which will later impact environmental preservation, is why this research aims to examine the impact of local wisdom-based E-module "Sasi" on students' scientific literacy and environmental care attitudes. The research method used was quasi-experimental with a nonequivalent posttest-only control group design. The concentration of this research was PGSD students taking basic science concepts courses, with 120 students divided into four classes. Data collection is done through tests and questionnaires. Data analysis includes descriptive analysis and inferential statistical analysis. The analysis results show that learning with e-modules based on local wisdom sasi is effective in developing scientific literacy and an attitude of caring for the environment, both as a whole and separately, with a value of Sig. <0.05. It shows that e-modules based on local wisdom sasi are effectively used in learning basic science concepts. This research supports holistic and sustainable learning in developing scientific literacy and environmental awareness.